Acoustic and Perceptual Characteristics of Compressed Dysarthric Speech: Implications for Teleassessment. - Tran, Kelvin; Utianski, Rene L.; Berisha, Visar; Liss, Julie M. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study aimed to evaluate how speech signal compression algorithms affect the acoustic and perceptual characteristics of dysarthric speech. As telepractice becomes more common in speech-language pathology, particularly in the assessment of dysarthria, understanding the impact of telecommunication compression on speech fidelity is essential for clinical decision making. Method: Speech samples were collected from 15 individuals with dysarthria, recorded locally and simultaneously via Zoom (Version 6.2.11). The Opus codec was used to process the locally recorded speech samples under fullband, wideband, and narrowband compression conditions. Acoustic measures were derived for all samples. Twenty experienced speech-language pathologists (SLPs) rated vocal quality and nasality for sustained vowels and rated articulatory precision and orthographically transcribed sentences across each condition. Results: Narrowband compression was associated with significantly degraded voice quality measures (e.g., harmonic-to-noise ratio, shimmer) and reduced transcription accuracy. Despite these changes in acoustics and intelligibility, ratings of articulatory precision, nasality, and vocal quality remained stable across conditions, suggesting SLPs could adjust for compression artifacts when making perceptual judgments. Conclusions: Speech compression, particularly in low-bandwidth (i.e., narrow) condition, impacts acoustic fidelity and intelligibility, though expert listeners maintain reliable perceptual judgments. These findings underscore the need to consider compression effects in telepractice and highlight the importance of developing optimized protocols for remote dysarthria assessment.